Learning physics in a Taiwanese college classroom: a constructivist perspective - Ying, Wai Tsen (Curtin University, 2008)
The purpose of this study is to use a constructivism as a referent to investigate how students learn physics in a Taiwanese career college classroom. Forty-nine first year, engineering major first students participated in this study of teaching and learning in my college level classroom. The theoretical framework for the study was based on the five dimensions of the Constructivist Learning Environment Survey (CLES) (Taylor & Fraser, 1991: Taylor, Fraser & White, 1994; Taylor, Fraser & Fisher, 1997), namely Personal Relevance, Student Negotiation, Shared Control, Critical Voice, and Uncertainty. These dimensions were employed as analytic themes to examine the qualitative data.A total of six lessons were observed: two lecture classes, two laboratory practice sessions, and two group discussion sessions. My qualitative observations, supplemented by video- and audio-recordings, of these six lessons were used to produce six classroom narratives. These six narratives were analyzed individually and then comparatively using a cross case analysis whereby the five dimensions of the CLES were employed as analytic themes. The CLES questionnaire was administered at the commencement of the semester and again at the end of the semester in order to determine any quantitative changes in students’ perceptions of their classroom environment. The various analyses were used to make several propositions about the constructivist nature of my classroom. I conclude the study with a discussion of the implications of the study and my reflections on the thesis experience.The study found that, in my Taiwanese career college physics classroom, (a) the teacher plays a central role in establishing the overall classroom learning environment, (b) student group dynamics are important in the classroom learning environment, (c) the central role of content often works against the establishment of a constructivist classroom, (d) cultural factors play a large role in determining the constructivist nature of the classroom, (e) language plays an important role in the construction of the learning environment, and (f) the students’ learning attitude affected the classroom environment.